2008
DOI: 10.1136/adc.2008.138768
|View full text |Cite
|
Sign up to set email alerts
|

A week-by-week analysis of the low-risk criteria for serious bacterial infection in febrile neonates

Abstract: LRC are not sufficiently reliable to exclude the presence of SBI, including bacteraemia and meningitis in febrile neonates of all ages. All febrile neonates should therefore be hospitalised, undergo a full "sepsis evaluation" and receive empirical intravenous antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
44
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 31 publications
(41 reference statements)
7
44
1
2
Order By: Relevance
“…This is higher in infants aged 0-28 days (9-28%) than those 2-3 months old (7.1%) [2][3][4][5][6][7][8][9]15,16]. We found the overall rate of SBI was high (38.4%) and our findings confirmed that SBI was seen more frequent in the neonatal period.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This is higher in infants aged 0-28 days (9-28%) than those 2-3 months old (7.1%) [2][3][4][5][6][7][8][9]15,16]. We found the overall rate of SBI was high (38.4%) and our findings confirmed that SBI was seen more frequent in the neonatal period.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, UTI was found higher and reported that 14-21.3 percent in febrile neonatesthat means UTI affects approximately 1 in 6 febrile neonates [2][3][4][5][6][7][8][9][10][11]18]. In our study, UTI incidence was found similarly the most common etiology of fever in neonatal period.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…[7][8][9] A recent study of febrile neonates concluded that lowrisk criteria are not sufficiently reliable to exclude the presence of SIs in febrile neonates in any age category under 28 days. 10 They recommend that all febrile neonates #28 days of age should therefore be hospitalized, undergo a full sepsis evaluation, and receive empirical intravenous antibiotic therapy. Garcia et al 11 evaluated whether 15 days was an appropriate cutoff for considering SI in the management of febrile neonates and concluded that febrile neonates 15 to 21 days of age had a rate of serious bacterial infection similar to that of younger infants and higher than that of older infants.…”
mentioning
confidence: 99%